2018
DOI: 10.1080/2162402x.2018.1461304
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis reveals the specific clinical and immune features of B7-H3 in glioma

Abstract: Background: B7-H3 is an immune checkpoint member that belongs to B7-CD28 families and plays a vital role in the inhibition of T-cell function. Importantly, B7-H3 is widely overexpressed on solid tumors, making it become an attractive target for cancer immunotherapy. To clarify the expression panel of B7-H3 in glioma, we explored the clinical and immune features of B7-H3 expression in a large-scale study. Methods and patients: Totally, 1323 glioma samples from Chinese Glioma Genome Atlas (CGGA) dataset, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 35 publications
5
56
0
Order By: Relevance
“…Accumulating evidence indicates that B7-H3 is present abundantly in several tumor types and participates in the immunosuppression and tumor progressions. [19][20][21] In the present study, we observed restricted expression of B7-H3 in tumor tissues from low-malignant patients, but enriched expression in those ovarian tumor tissues from high-malignant patients. The expression of B7-H3 also induces the stem-like phenotypes and drugs resistance of ovarian cancer cells in vitro and vivo, which is consistent with precious reports in prostatic cancer and bladder cancer.…”
Section: Discussionsupporting
confidence: 61%
“…Accumulating evidence indicates that B7-H3 is present abundantly in several tumor types and participates in the immunosuppression and tumor progressions. [19][20][21] In the present study, we observed restricted expression of B7-H3 in tumor tissues from low-malignant patients, but enriched expression in those ovarian tumor tissues from high-malignant patients. The expression of B7-H3 also induces the stem-like phenotypes and drugs resistance of ovarian cancer cells in vitro and vivo, which is consistent with precious reports in prostatic cancer and bladder cancer.…”
Section: Discussionsupporting
confidence: 61%
“…B7-H3, the only commonly elevated ligand by NZB11 and NZB19 gCSCs, expression correlates with glioma grade and negatively correlates with T-cell mediated immune response to glioma (41,42). While B7-H3 expression has not been well characterised on glioma cancer stem cell subsets beyond this study, the elevated expression here suggests to a mechanism by which B7-H3 expression on GBM cancer stem cells could drive worsening prognosis through enhanced immunological inhibition.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, we sought to examine the correlation between the risk score and immune checkpoints expression. We altogether enrolled 30 immune checkpoints in our analysis, including TNF superfamily (BTLA, TNFSF14, CD40, TNFRSF4, TNFRSF9, CD27, CD40LG, TNFSF4, TNFSF9, CD70 and TNFRSF18) [17], B7-CD28 family (CD274, PDCD1LG2, ICOSLG, CD276, VTCN1, HHLA2, CTLA4, ICOS, PDCD1, and TMIGD2) [18,19], and other immune checkpoint members (HAVCR2, IDO1, LAG3, FGL1, ENTPD1, NT5E, SIGLEC15, C10orf54 and NCR3) [20][21][22]. The heatmap for immune checkpoints expression was produced, taking other clinical characteristics into consideration, such as sex, age, TNM stage, and lymphatic metastasis (Fig.5B).…”
Section: Relationship Between the Risk Score And Immune Landscapesmentioning
confidence: 99%